HEDONIC AND UTILITARIAN CONSUMPTION WITH COMPULSIVE BUYING RELATIONSHIP USE OF CREDIT CARD: A RESEARCH ON ONLINE MARKETPLACE - Bayır, Talha (My University, 2021)
The scope of this research is to examine the effect of utilitarian and hedonic consumption on compulsive purchases and regret levels through uncontrolled credit card usage. The sample group of the research consists of 466 online shopping consumers. In this context, descriptive statistics and validity and reliability analysis of the data were performed. After confirmatory factor analysis, PATH analysis were applied. According to the findings obtained as a result of the research; hedonic consumption, uncontrolled credit card usage and compulsive buying positively affected; utilitarian consumption negatively affects compulsive purchasing through uncontrolled credit card usage. In addition, uncontrolled credit card usage affects compulsive purchasing; compulsive buying affects regret.
Keywords: Hedonik Tüketim; Faydacı Tüketim; Kompulsif Satın Alma; Kredi Kartı Kullanımı; Pişmanlık